Healthcare experiences and barriers for Men Who Have Sex with Men - MSM - who engage in chemsex. (2022) - Tangerli, M.M.; Godynyuk, E.A.; Gatica-Bahamonde, G.; Neicun, J.; Van Kessel, R.; Roman-Urrestarazu, A.
Abstract: Background: Chemsex refers to the use of drugs (e.g. mephedrone, gamma-hydroxybutyrate (GHB)/gamma-butyrolactone (GBL), methamphetamine, and ketamine) before or during sexual activity. Men who have sex with men (MSM) are a population in which chemsex engagement is prevalent. This poses risks of harm for mental and psychosocial health resulting in the use of healthcare services. This review aims to analyse the extent to which current prevention and harm reduction strategies concerning chemsex meet the healthcare needs of MSM who engage in chemsex in France, Germany, the Netherlands, Spain, and the United Kingdom. Methods: Published papers reporting prevention and harm reduction interventions concerning MSM who engage in chemsex were identified through PubMed and Scopus. By utilising a holistic care perspective, data was synthesised concerning social norms within the MSM community, experiences with care providers, healthcare needs, experienced barriers to seek care, and structural barriers to providing care. Results: Literature search identified 154 unique publications, of which 17 were included in the data synthesis. The cultural acceptance of drug use in both sexual and non-sexual contexts is high within the MSM community. Whereas there is a lack of awareness of chemsex-specific care by sexual health clinics (SHCs), standard drug and health clinics are often experienced negatively. The ability of SHCs to offer support tailored to the needs of MSM who engage in chemsex is often limited by lack of training or lack of referral chains. Conclusion: As the MSM community and especially MSM who engage in chemsex are quick to adapt to new drug trends, it is important to increase support system resilience for chemsex care. There is a need for training, interorganisational cooperation, and expertise sharing and awareness of quality chemsex services and information. Integrated chemsex care, rapid referral chains, and their evaluations are required to align provided care with healthcare preferences.